(untitled) (Research, Society and Development, 2021)
Currently, we observe na increase in the chronicity of non-communicable diseases, raising the estimate of population life and showing the existence of the disease process that leads to finitude life. Automatically arises the need to establish a processo f assistance and education to Palliative Care, symbolizing the improvement of the Death and Dying system. Objective: Knowing that information comprises a fundamental elemento in the processo of developing Permanent Health Education for work in patient care, the exeperience in the construction of an educational booklet about Palliative Care in na emergency hospital in the city of Rio de Janeiro is portrayed as a knowledge vector. Methodology: A descriptive research was carried out on the need for knowledge by nursing professionals on the topic of Palliative Care, which became the trigger for the construction of this booklet. Results and discussion: After evaluating the application of material, it was possible to perceive it as aggregating material for interdisciplinar knowledge in a multidisciplinar team.